MParCO: A Minimalist Parallel Framework for Combinatorial Optimization Applications - Dantas, Allberson B. de O.; Corrêa, Ricardo C.; de Vasconcelos, Lucas B. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2018)
This paper addresses the exploration of the potential of distributed parallelism in combinatorial optimization applications through a minimalist approach. In contrast to several parallel frameworks proposed in the last decades, specialized in parallelizing classical methods such as Branch-and-Bound and well-known metaheuristics, we propose a framework, so-called MParCO, that focuses essentially on assuring asynchronism, an essential ingredient for the performance of enumerative methods for combinatorial optimization problems.